Peningkatan Kualitas Pelayanan Kader Kesehatan TBC Desa Grujugan Melalui Pembuatan Aplikasi Lapor TBC - Yuliastina, Roos; Ahmaniyah, Ahmaniyah; Liyanto, Liyanto (Universitas Nusantara PGRI Kediri, 2022)
Indonesia ranks 3rd as the country with the most tuberculosis (TB or TB) sufferers in the world, after India and China. To support international programs and reduce the number of TB spreads in Indonesia, one of the areas designated as TB Alert village since 2021 is Grujugan Village, Gapura District, Sumenep Regency. Based on data from the Gapura Health Center in 2020, the Gapura Community Health Center contributed 3.5% of the total TB patients in Sumenep Regency, the main locus of TB patients in Gapura sub-district is Grujugan village. After being designated as a TB Alert village, the local village government formed 25 TB health cadres. In the process of screening, mentoring and supervising taking ODTB (People with TB) drugs in Grujugan village, several main problems were found; (1) The village government as the leading sector of TB eradication in Grujugan village does not have access to obtain the latest data regarding the total number and who the local population has screened for TB. (2) The village government receives data on the results of screening and TB suspects in the form of paper forms, so that the data received is only in the form of paper reports that are archived in a modest manner. (3) Supervision of taking medication for residents who are tested positive for TB is carried out manually, such as visiting ODTB's (People With TB) homes or reminding them via telephone. (4) There are still residents who are declared as ODTB stop taking medication, this is because ODTB experience anxiety, cold sweats, feel pain in several parts of the body after taking TB medication. (5) The community of Grujugan village is saturated with TB socialization activities carried out by TB health cadres, this is also because the health cadres have not received training in communication skills and self-healing to reduce anxiety for ODTB. This PKM implementation method is divided into four stages; (1) planning, (2) implementation: making the TB Report application as well as training & mentoring in communication skills, (4) activity evaluation and (5) PKM results reporting. The output of this service activity is to improve the service quality of TB health cadres in monitoring the spread of TB to be more effective up to 70% through the use of the TB Report application and improving communication skills for TB health cadres.